Cell biology for biotechnologists - Stanley, Shaleesha A (Narosa, 2008)
Cell Biology for Biotechnologists enumerates the basic structure of prokaryotic and eukaryotic cells and the exceptions for cell theory and explains the mechanisms of transport within and out of the cell, the receptors and their role in signal transduction and cell culture. The major emphasis of today’s biotechnologists is to explore the signal transduction pathways making use of G proteins, MAP kinases and phosphatases explained in this book. In the last chapter cell culture and maintaining cell lines, stock cells and techniques for propagation methods are discussed. This volume is written with the primary objective of educating the molecular aspects of a cell to the undergraduate and post graduates students of various disciplines such as biology, biotechnology, veterinary medicine and life sciences.